Effectiveness of Square Stepping and Weighted Vest Training on Fall Prevention among Ambulatory Community Dwelling Elderly - Dr.I.Deepa, Jayadharshini Elango, Renuka Sundar, Ahalya K P, 5Kirthika.R, Pavithralochani V (South Eastern European Journal of Public Health, 2024)
Background: Falls are a major cause of injuries and dependence among older adults living in the community, and they often result in age-related deficits in balance, strength, and functional mobility. Interventions that address these characteristics are critical for fall prevention. Square Stepping Exercise (SSE) enhances dynamic balance and coordination by using multidirectional stepping patterns, and Weighted Vest Exercise adds resistance to increase muscle strength and bone density. Combining SSE and WVE may provide a more comprehensive approach to reduce fall risk. This study investigates the efficacy of these exercises in increasing balance, strength, and mobility, hence preventing falls among ambulatory elderly. Method: This experimental study was conducted on 70 older adults living in the community. Participants were chosen according to specific inclusion criteria and randomly assigned to either an experimental group (n=35) or a control group (n=35). Participants in experimental group performed square stepping exercise along with weighted vest training for duration of 30 minutes per session for 6 weeks. Pre and post-test evaluation were done using Berg balance scale, Time up and go test and Five times sit to stand Test. Result: The study results indicated a statistically significant difference in the mean and standard deviation, within the Groups for the outcome measures (p < 0.0001). On comparison between the post-test mean value, square stepping exercise group showed more improvement on Balance, Strength and Functional mobility. Conclusion: Square stepping exercise along with weighted vest exercise is a simple, home based and effective way on improving balance and strength also preventing falls among elderly population.